2020
DOI: 10.1155/2020/2529816
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Conflict Analysis of Motor Vehicles and Nonmotor Vehicles Based on Improved Cellular Automata

Abstract: In recent years, with the rapid development of China's logistics industry and urban service industry, electric bicycles have gradually become an important means of transportation in cities due to their flexibility, green technology, and low operating costs. Because electric bicycles travel though motor vehicle lanes and nonmotor vehicle lanes, the conflict between motor and nonmotor vehicles has become increasingly prominent, and the safety situation is not optimistic. However, most theories and models of mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Therefore, this result is satisfactory, when comparing the accident rate (2.4) with that of Chenhao Dong et al [81] (2.159) as, without an APAS solution (which is similar to a physical isolation divider), the risk is higher.…”
Section: Experiments 2: Comparing the Apas Algorithm With The Action ...mentioning
confidence: 65%
See 3 more Smart Citations
“…Therefore, this result is satisfactory, when comparing the accident rate (2.4) with that of Chenhao Dong et al [81] (2.159) as, without an APAS solution (which is similar to a physical isolation divider), the risk is higher.…”
Section: Experiments 2: Comparing the Apas Algorithm With The Action ...mentioning
confidence: 65%
“…As presented in the introduction, there are four problems that motivated this study: those of TS vs. use of TG for DSs, challenges associated with integrating TGs with DSs, the need for the realistic simulation (physics and behaviors) of traffic, and the simulation of mixed traffic flow in over-populated/under-developed/under-regulated traffic. Among previous studies concerning the safety of mixed traffic flow, Chenhao Dong et al [81] have compared the conflict rate of mixed traffic flow before and after applying a physical isolation divider. Their results indicated that a mixed traffic flow is more dangerous than a single flow, as depicted in Figure 5a from [81].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations